Parkett : The Parkett series with contemporary artists. (Zürich : Parkett-Verlag, 1993)
Table of Content : Jana Sterbak, Chaos and Self-Creation by Richard Noble ; Max Neuhaus, Insvisible Sculpture – Molded Sound by Doris von Drathen ; Gerhard Richter : Three Impromptus on the Art of Gerhard Richter by Jean-Pierre Criqui ; Endless Finalities by Peter Gidal ; The Tragic Desire by Birgit Pelzer ; Sequence of Time by Gertrud Koch ; Richter in Tahiti by Dave Hickey ; Barbara Bloom, Insert : Lèche-Vitrine by Peter Fleissig ; Dieter Roth, Garbage Clarified by Patrick Frey ; Meyer Vaisman Flips the Brid by Trevor Fairbrother ; Anne Teresa de Keersmaeker in New York 1991/1992, Les Infos du Paradis by RoseLee Goldberg ; On Differences in the Place of the Work, Cumulus from Europe by Hans Rudolf Reust ; Cumulus from America by Paul Taylor ; Kawamata’s Miracle by Claudia Gould
Of Rivers and Office Chairs. The picture on the cover of this issue is number 67 in a series of 115 paintings created by Gerhard Richter for the readers of Parkett. The title of the series, Green-Blue-Red, makes laconic reference to the basic elements of a highly consequential painting operation. Further scrutiny of the suite of paintings yields insight into the idea of a perfected diversity or into what author Peter Gidal calls “endless finalities.” The outcome is a flow of pictures each of which will remain part of a “closed circuit,” even as they are sent out into the world. We are pleased and proud to have been able to participate in the actualization of this project. (editorial by publisher)
boek
Keywords: Richter, Gerhard